The Relationship Between Self-Directed Learning and Learning Motivation Towards Mathematics Achievement of Elementary School Students in SD Negeri 03 Karangasem - Ravikasha Azka Azkiya; Sukartono Sukartono (Eduvest - Journal of Universal Studies, 2024)
This research has the following objectives; 1) Knowing the relationship between independence and learning achievement of low grade students; 2) Knowing the learning motivation of low class students' learning achievement; 3) To find out the joint relationship between independence and learning motivation on the learning achievement of low grade students at SDN 03 Karangasem. This research uses quantitative descriptive research with a correlation design. The research sample consisted of 23 lower class students. The data collection technique uses a valid questionnaire. Test the prerequisites using the normality test and the Kolmogorov Smirnov linearity test. The simple linear regression hypothesis test uses the t test while the multiple regression test uses the F test. The research results show that; 1) There is a significant relationship between learning motivation and mathematics learning achievement of low class students with a significance value of 0.013 at a significance level of 0.05. 2) There is a significant relationship between learning independence and the mathematics learning achievement of low grade students with a significance value of 0.032 at the 0.05 significance level. 3) There is a relationship between learning motivation and learning independence on the mathematics learning achievement of low class students at SD Negeri 03 Karangasem with the F test results in hypothesis testing of 0.000 at a significance level of 0.05.